Splitting tensile strength study of tin slag polymer concrete - Muhamad Soffi, Manda; Mohd Ruzaimi, Mat Rejab; Shukur, Abu Hassan; Mat Uzir, Wahit; S. S., Amirnuddin (Elsevier Ltd, 2023)
Tin Slag Polymer Concrete (TSPC) compressive strength has achieved 58.21 MPa which is an acceptable limit for structural application. However, there was insufficient information on the tensile strength of TSPC whereas tensile parameter is also important to provide an indicator of cracking failure estimation and numerical analysis application. Therefore, experimental study has been performed to examine splitting tensile strength of TSPC. Findings show that average splitting tensile strength for TSPC is 6.08 MPa which is about 10.44 % from TSPC compressive strength. The specimen also has shown brittle failure where fracture occurs with small deformation. The failure mechanism of TSPC share similar pattern with all specimen experience primary and secondary crack. Fractured surface of the specimen ST-1 shows smooth and flat while ST-3 shows rough, burst and scattered. In general the study on TSPC splitting tensile strength has found several findings includes average splitting tensile strength, average tensile modulus, TSPC brittle behavior, fractured surface as well as the primary and secondary crack formation during experimental test.